Changes in Racial and Ethnic Disparities in Estimated Diagnosis Rates of Heterosexually Acquired HIV Infection Among Heterosexual Males in the United States, 2014–2018. (15th December 2020) - McCree, Donna Hubbard; Chesson, Harrell W.; Eppink, Samuel T.; Beer, Linda; Henny, Kirk D.
Abstract : Background: Diagnoses of HIV infection among male adults and adolescents ≥13 years with infection attributed to heterosexual contact decreased from 2014 through 2018. Racial disparities exist; HIV diagnoses are higher among Black/African American men compared with men of other races/ethnicities. In 2018, Black/African American males accounted for 61% of diagnosed HIV infections attributed to heterosexual contact among males. Setting: We used national HIV surveillance data from Atlas Plus to obtain the annual case counts of new HIV diagnoses in males with infection attributed to heterosexual contact and population size for years 2014 through 2018 for males (United States excluding territories) by the racial/ethnic group. Methods: We used an adjusted population denominator to calculate rates of diagnoses of HIV infection acquired through heterosexual contact per 100, 000 males and 12 absolute and relative measures of disparity to calculate racial/ethnic disparity changes from 2014 to 2018. Results: Results from all disparity measures indicate that disparities decreased in 2018, compared with 2014. The decreases ranged from 18.8% to 34.6% among the 4 absolute disparity measures and from 5.3% to 22.7% among the 8 relative disparity measures. Conclusions: Despite the decrease, disparities remain. Tailored, effective strategies and interventions are needed to address the social and structural factors associated with HIV risk among heterosexual Black men and to promote continued progress toward reducing disparities.